Prognostic value of post-treatment 18F-FDG PET/CT for advanced head and neck cancer after combined intra-arterial chemotherapy and radiotherapy - Ito, Kimiteru; Shimoji, Keigo; Miyata, Yoko; Kamiya, Kouhei; Minamimoto, Ryogo; Kubota, Kazuo; Okasaki, Momoko; Morooka, Miyako; Yokoyama, Jyunkichi (Chinese Journal of Cancer Research; Vol 26, No 1 (February 27, 2014): Chinese Journal of Cancer Research, 2014)
Objective: To clarify the prognostic value of post-treatment 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) in patients with advanced head and neck squamous cell carcinoma (HNSCC) after combined intra-arterial chemotherapy and radiotherapy (IACR). Methods: Thirty-six patients with HNSCC who underwent IACR were recruited. The period from the end of IACR to the last post-treatment 18F-FDG PET/CT examination was 8-12 weeks. Both patient-based and lesion-based analyses were used to evaluate the PET/CT images. For lesion-based analysis, 36 regions (12 lesions of recurrences and 24 scars at primary sites) were selected. The Kaplan-Meier method was used to assess the overall survival (OS) stratified by 18F-FDG uptake or visual interpretation results. Results: Twelve patients with recurrence were identified by six months after IACR. The sensitivity and specificity in the patient-based analysis were 67% (8/12) and 88% (21/24), respectively. The mean OS was estimated to be 12.1 months (95% CI, 6.3-18.0 months) for the higher maximum standardized uptake value (SUVmax) group (n=7) and 44.6 months (95% CI, 39.9-49.3 months) for the lower SUVmax group (n=29). OS in the higher SUVmax group (cut-off point, 6.1) or positive visual interpretation group was significantly shorter than that in the lower SUVmax or negative visual interpretation group (P